Reading And Writing: An Integration Of Skills - Jiménez Tassara, Alejandro (2021)
The importance of approaching the basic linguistic skills reading, writing, listening and speaking, as a group of abilities that must be taught in an integrated way should always be reflected in any lesson plan for an EFL teaching class.